The Labor of Care : Filipina Migrants and Transnational Families in the Digital Age - Francisco-Menchavez, Valerie, 1983- (Book collections on Project MUSE., 2018)
"The nature of transnational families is such that separated members, both abroad and home, consistently craft strategies of care through technology and multidirectional care work to cope with the difficult sacrifice of migration. This book is about the affliction of migration and globalization and the durability of families through these circumstances. It provides accounts of the impact of global care chains on the families of migrant women from the Philippines and the emergence of new forms of intimacies and care work as the women navigate and negotiate the emotional and material consequences of family separation and the resulting shifts in family gender dynamics. Drawing on extensive fieldwork, Francisco presents the self-care perspective of women of color feminism by showing the multidirectional care work that occurs with migration and investigates the changes in family that come with migration and circumstances where migrants are separated from their families because of legal or economic reasons. Anchored in the experiences and lives of Filipino migrants and their families in the Philippines, it also describes the lives of many families from the Global South who are separated from one another. Francisco highlights the way in which new technologies have become central to the reconfiguration of family and how Facebook, Skype, and recorded videos and pictures are important components in the lives of migrant mothers and their families left behind. Francisco analyzes the formation of extended communities of migrant mothers and the fictive kinships that women apart from families of origin create abroad in their mother work abroad"--